Prevalence Of Schizophrenia Incident Rates Based On Age And Gender In RSKD Dadi South Sulawesi Province In 2022 - Rifqha Dwiputri Ilham; Wahidah Jalil; Hidajah, Hidajah; Irma Santy; R. Joko Maharto (Jurnal EduHealth, 2024)
Schizophrenia is a serious mental disorder that affects individuals globally, causing significant cognitive, emotional, and behavioral dysfunction. Although the prevalence of schizophrenia has been widely studied, understanding the distribution of the incidence of this disease based on age and gender still requires further research. To determine the prevalence of schizophrenia incidence rates based on age and gender in RSKD Dadi, South Sulawesi Province in January-December 2022. This research is a descriptive analytical study with a retrospective study method with the aim of knowing the prevalence of schizophrenia incidence rates based on age and gender in RSKD Dadi, South Sulawesi Province in 2022. The highest percentage of Schizophrenia cases in RSKD Dadi, South Sulawesi Province who were hospitalized in January-December in 2022 based on age, the highest was >50 years old, namely 818 cases (76.4%), based on type gender, namely men as many as 835 (78.0%).